It is a straight line equation that can be rearranged into slope intercept form:
-x+2y = 12
2y = x+12
y = 0.5x+6 which is now in slope intercept form
x = -4 and y = 4
Both of them are equations!The solution is (x, y) = (2, 1).
(12, 1)
If the two equations are (i) 4x + 2y = 12 and (ii) x + 2y = 6, proceed as follows: Rewrite (ii) as x = 6 - 2y; substitute this expression for x into (i) to result in 4(6 - 2y) + 2y = 12, or 24 - 8 y + 2y = 12, or - 6 y = 12 -24 = -12, or y = -12/-6 = 2. Then, back to (ii) again, x = 6 - 2(2) = 2.
This means that 2y - 3 = 2y + 4 which is not possible.
x = -4 and y = 4
Both of them are equations!The solution is (x, y) = (2, 1).
(12, 1)
If the two equations are (i) 4x + 2y = 12 and (ii) x + 2y = 6, proceed as follows: Rewrite (ii) as x = 6 - 2y; substitute this expression for x into (i) to result in 4(6 - 2y) + 2y = 12, or 24 - 8 y + 2y = 12, or - 6 y = 12 -24 = -12, or y = -12/-6 = 2. Then, back to (ii) again, x = 6 - 2(2) = 2.
x = 11/7 and y = 12/7
This means that 2y - 3 = 2y + 4 which is not possible.
-2y=x+8 is the answer
2y(x+2)=
x = -8, y = 10
They are straight lines.
perpendicular
x = 3y - 3 so 6 (3y - 3) + 2y = -12 ie 18y - 18 + 2y = -12 ie 20y = 6 so y = 0.3 and x = -2.1